THE USE OF MULTIMEDIA FOR FACILITATING LEARNING STYLE DIFFERENCES IN BALANCING REDOX REACTIONS - Sukarmin - (PROSIDING SEMINAR KIMIA, 2015)
This study aims to determine, the distribution of students' learning styles, student responses to multimedia, and the improvement of learning outcomes after using multimedia. By using instruments The Kolb Learning Styles Inventory was found that from 15 students in the research class is divided into 20% diverger, assimilator 13.3%, 20% converger, and 46.7% accomodator. The results of this research showed that students with diverger, assimilator, diverger, and converger learning styles gave a positive response. Multimedia is suitable to be applied to the student's learning style diverger, assimilator, diverger, and converger with high learning outcomes improvement.